2020
DOI: 10.1177/0164027520958582
|View full text |Cite
|
Sign up to set email alerts
|

Do Aging Employees Benefit from Self-Regulative Strategies? A Follow-Up Study

Abstract: SOC-strategies (selection, optimization, and compensation) are crucial for well-being and adaptation throughout the life course. The workforce is aging rapidly, thus the age-conditional premises of SOC theory require attention. This study explored (1) whether older employees used SOC strategies more often (compared to younger employees), and (2) whether older employees benefited more from SOC strategies in relation to occupational well-being (job burnout, work engagement). The study was based on follow-up data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(214 reference statements)
0
1
0
Order By: Relevance
“…SOC strategies may be applied in response to a reduction in resources caused by developmental changes, as well as external changes, such as organisational changes, throughout the career. Although some studies have found that older workers benefit more from the use of SOC strategies than younger workers [ 2 , 10 , 23 ], other studies have found that workers across all age groups benefit from the use of SOC strategies [ 13 , 21 ]. von Bonsdorff [ 6 ] even found that the strength of the association between the use of SOC strategies and work ability was stronger among younger than older nurses.…”
Section: Introductionmentioning
confidence: 99%
“…SOC strategies may be applied in response to a reduction in resources caused by developmental changes, as well as external changes, such as organisational changes, throughout the career. Although some studies have found that older workers benefit more from the use of SOC strategies than younger workers [ 2 , 10 , 23 ], other studies have found that workers across all age groups benefit from the use of SOC strategies [ 13 , 21 ]. von Bonsdorff [ 6 ] even found that the strength of the association between the use of SOC strategies and work ability was stronger among younger than older nurses.…”
Section: Introductionmentioning
confidence: 99%